School principal's leadership style and the school culture : a case study - Mahmassani, Salwa (Beirut Lebanese American University- School of Arts and Sciences - Department of Education., 2007)
A case study was conducted in a private school in United Arab Emirates to identify the leadership style of the principal, whether it was transformational or transactional, and to examine its effect on some aspects of the school culture. The principal and all staff members filled a modified questionnaire created by Avolio and Bass (2004) and aimed at revealing the school principal's leadership style as viewed by the stakeholders. Semi-structured interviews and observations were also conducted. Throughout the study, documents were also collected to check whether they reflect the information collected via the other instruments. Qualitative and quantitative data analysis was conducted and findings showed that the principal had a mixture of both transformational and transactional leadership styles which positively affected some aspects of the school culture namely school mission, vision, collegiality, professional development and teacher-parent relationships. The study findings were in harmony with the intemationalliterature on the impact of leadership styles of school principals.
: Mémoire
Keywords: Gestion scolaire; Leadership; Leadership; School management